(3eLehYI aj GdgfOSIs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s
(3ChdgG (B:s
(3hgj SJI hKdGKhf TcdkG hai HYV GdfSN CQHYI hKdGKhf TcdkG Ydi GdJQJjH GdeKHJ HGdCQbGe s
(3BNQgG (B:s
(3hPdc eG CQOfGg ef GdeaQhVGJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeS YTQs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1461s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdQjGVjGJs